Thermal adaptation a theoretical and empirical synthesis - Angilletta, Michael J. (Michael James) (Oxford : Oxford University Press, 2009)
Temperature impacts the behaviour, physiology and ecology of all organisms more than any other abiotic variable. In this text the author draws on theory from the more general discipline of evolutionary ecology to foster a fresh approach toward a theory of thermal adaptation.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Heat adaptation